Gawad Plaridel lecture 2016 - Custodio, Francisca; Enriquez, Elizabeth L. (2018)
Access online through this link: https://www.plarideljournal.org/article/gawad-plaridel-lecture-2016
Keywords: UP Gawad Plaridel; Award presentations